Experimental studies on the thermal conductivity of methyl laurate component of biodiesel with three alcohols. (December 2019) - Fan, Jing; Cui, Bin; Liu, Shuangshuo; Song, Fenhong; Wang, Xiaopo
Highlights: Measurement of thermal conductivity of five Aliphatic esters was carried. The thermal conductivity of five aliphatic esters is reported for the first time. Comprehensive comparison was made about the thermal conductivity of ten esters. Abstract: Biodiesel has been considered as one of the feasible attempts to replace the fossil fuels. Alcohols always played a role as the additives to improve the certain properties of biodiesel. In this work, the liquid thermal conductivity of binary mixtures of methyl laurate usually the significant biodiesel component with three alcohols (1-propanol, 1-butanol and 1-pentanol) was measured with the temperature ranging within 287 K to 358 K at atmospheric pressure. The total standard uncertainty of the experimental results was estimated to be less than 2% (in the 0.68 confidence level) and the repeatability was better than ±0.5%. In addition, three useful correlations for estimating the thermal conductivity of mixtures have been fitted and optimized, and the maximum deviation of three correlations were less than 1.30%.